Spillovers in Criminal Networks: Evidence from Co-offender Deaths - Matthew J. Lindquist; Eleonora Patacchini; Michael Vlassopoulos; Yves Zenou (Institute of Labor Economics (IZA), 2024)
We study spillover effects within co-offending networks by leveraging deaths of co-offenders for causal identification. Our results demonstrate that the death of a co-offender significantly reduces the criminal activities of other network members. We observe a decaying pattern in the magnitude of these spillover effects: individuals directly linked to a deceased offender experience the most significant impact, followed by those two steps away, and then those three steps away. Moreover, we find that the death of a more central co-offender leads to a larger reduction in aggregate crime. We also provide evidence consistent with a new theoretical prediction suggesting that the loss of a co-offender shrinks the future information set of offenders, altering their perceptions of the probability of being convicted and consequently affecting their criminal behavior. Our findings highlight the importance of understanding spillover effects for policymakers seeking to develop more effective strategies for crime prevention.
Keywords: A14; D85; K42; Z13; 330; networks; crime; key players; exogenous deaths; spillovers